Memahami Literasi Keuangan sebagai upaya Pencegahan Perilaku Konsumtif dari Pinjaman Online - Askardiya Mirza Gayatri; Muzdalifah Muzdalifah (JUDICIOUS, 2022)
The increasing number of users of online loan services (pinjol) is in line with the proliferation of finance service companies. Many have been helped by this loan facility, but not a few have become victims as a result of being unwise and not careful in choosing a loan company and in utilizing the funds. The percentage of types of online loans is because their use is more flexible for any purpose, both consumptive and productive. Even though the socialization of loan services with various media is always echoed, there are still many who do not understand so that it has an impact on the psychological side of loan service users such as stress and depression. The purpose of this study is to educate the public so that they understand financial literacy in the field of financial technology (fintech), one of which is online lending in an effort to prevent consumer behavior. This study method is an idea based on several references to previous studies, therefore the method used in this study is a literature study. With detailed and systematic reviews of previous publications related to the topic under study, namely financial literacy.